Measuring early reading skills using valid and reliable instrument - Fatkhur Rizki Raharjo; Fery Muhamad Firdaus; Rahmat Fadhli (Universitas PGRI Madiun, 2023)
Reading is an important language skill and plays a role in students' learning success. Reading success is driven by adequate early reading skills. To measure early reading skills, valid and reliable measurement tools were needed. The purpose of this study was to assess the construct validity and construct reliability of a newly designed early reading instrument. Using quantitative methods, 320 respondents from 17 randomly selected elementary schools were involved in the study. Using the Lisrel 8.80 program, the obtained data was analyzed using second-order confirmatory factor analysis. The findings revealed that the early reading skills instrument was valid in terms of loading factor, convergent validity, and discriminant validity, as well as meeting the construct reliability requirements, so that the developed early reading skills instrument was feasible to use.